Efficiency Development Analysis Use of Automation Testing using Katalon on Mobile-Based Applications (Case Insurance Company) - Anggrainy, Shynta Eza; Muhammad, Alva Hendi (IJISTECH (International Journal of Information System and Technology), 2024)
The use of automation in mobile application testing has become an important tool in improving the efficiency and quality of applications. Katalon Studio, as one of the automated testing tools, offers convenience for testers in conducting automated testing without having to master any programming language. This tool allows continuous testing to maximize the potential of features and applications as a whole. Katalon Studio also allows the addition of an alert feature on failed scenarios, so that the relevant team will be notified if a failure occurs when the script is run. In addition, the use of automated testing tools such as Katalon Studio can speed up the testing process and increase efficiency. In the context of mobile-based applications, automated testing is very important to ensure the quality of the user experience (usability). By conducting automated testing, the app design and development team can be aware of issues that may arise and fix them immediately. Overall, the use of Katalon Studio in automated testing of mobile applications can help improve the efficiency of the testing process and application quality, as well as maximize the potential of application features.